The definition of the state value in terms of functional quintessence - S. G. Pevko (Law and Safety)
The article examines the issue of the quintessence of the State's axiology in terms of functional definition. For the purpose of the study, the scientific issue is divided into components which are the substantive elements of the scientific problem. First of all, the issue of the essence of the State as a legal phenomenon is revealed, which is the main basis for the emergence of the scientific problem. The relevant views of scholars on the definition of the State are also considered. It has been concluded that the State is a sovereign, political and territorial organisation of society, on the territory of which there are authorities, legal system and taxation system, as well as other additional elements. The author further provides the features inherent in the State which constitute its ontology.